Enhancing Thermal Conductivity and Heat Transfer using Graphene Nanofluid - Mohammed Ridha H .Alhakeem (International Journal of Multidisciplinary Sciences and Arts, 2022)
Due to their low density and inherent thermal conductivity in compared to metals or metal oxides, carbon nanostructures among other nanoparticles exhibit better thermal conductivity. The ability of graphene Nano fluids to transmit heat has been studied in this work through a review of the findings of several studies. The current techniques for making graphene nanofluids have been summarized, along with several characteristics including viscosity, concentration, particle size, and temperature that have an impact on thermal conductivity. The convective heat transfer capabilities of graphene nanofluids have also been subjected to a careful analysis. The study shown that employing graphene nanofluids as a working fluid through a tube channel can improve heat transfer with considerable results. There hasn't been any research on the effects of graphene Nano fluids on facing steps and corrugated surfaces, according to the literature.